HUBUNGAN PENDIDIKAN DAN MASA KERJA DENGAN KETERAMPILAN PERAWAT MELAKUKAN TINDAKAN BANTUAN HIDUP DASAR - Vera Sesrianty (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Emergency nurses connect knowledge with skills to deal with life-threatening patients. The high number of emergency case visits such as respiratory arrest and cardiac arrest in each country is one of the impacts in the failure of emergency cases handling which is generally caused by failure to recognize risks, delays in handling, and lack of facilities and knowledge and skills of medical and paramedical personnel. Based on data obtained at the IGD and ICU RSUD Lubuk Sikaping, during 2016 there were 146 people experiencing emergency with the division of 62 people with respiratory failure, 52 heavy head injuries and 32 cardiac arrest, most died. The purpose of this research is to identify factors related to nurse skill in performing BHD action in IGD Room and ICU of Lubuk Sikaping Hospital. This research uses descriptive analytic method with corelation study approach design. Data processing using Chi Square test, with a sample of 30 respondents. The result of statistical test, it can be concluded that there is correlation of education level factor with BHD action, p value = 0,007 (p = P <α) the existence of time factor relationship with BHD action, p value = 0,000 (p <α) IGD Room and ICU of Lubuk Sikaping Hospital 2017. Suggestion in this research is the result of this research Can add insight and knowledge about the management of BHD properly so that emergency patients can be helped well.